Improving Student Learning Outcomes Through AMMan Teaching Module Development (Innovative R&D Study in Manufacturing Accounting) - Fauzan, Slamet; Wardoyo, Cipto; Putri, Arum Serina; Moliani, Ayuneng Indah (Social Science Studies, 2024)
Research Aims: This development research aims to develop accounting computer learning media (Accurate Manufacture).   Design/methodology/approach: This learning media was created using the R&D development model. The research design used a quasi-experimental approach with a one-group pretest-post-test design. The application is named “AMMan,” which generally includes Accurate Online Integration components that can be accessed via mobile, material, quizzes, interactive questions, and a teacher collaborative space.   Research Findings: The results of material and media expert validation with a score of 87.4%, limited users 84.6%, and students 87%, indicate that overall aspects are valid and feasible for use in learning activities. The research results through the paired sample t-test showed that the sig. The value of the cognitive domain was 0.001 less than the significance level of 0.05, so it can be stated that there are differences in learning outcomes before and after using learning media.   Theoretical Contribution/Originality: The difference indicates an increase in student learning outcomes, which, on average, increased by 21% in the cognitive domain. Thus, it can be stated that “AMMan” is effective in improving student learning outcomes at the student understanding level.